До виділення мосолівського горизонту доби пізньої бронзи євразійського степу та лісостепу - Пряхін, А.Д. (Археологія, 1997)
Мосолівський горизонт пам'яток доби пізньої бронзи займає проміжне місце між синташтинським (новоусманським) горизонтом та пам’ятками валикових культур та збігається з розвиненим етапом зрубної культурно-історичної спільності й алакульської культури. Для выделения Мосоловского горизонта памятников эпохи поздней бронзы использованы материалы эпонимного поселения, исследованного в лесостепном Подонье (Воронежская обл.). Основанием служит четкая стратиграфическая привязанность памятника. Нижние границы его бытования определяются, во-первых, тем, что поселению эпохи поздней бронзы предшествует поселок воронежской культуры эпохи средней бронзы; во-вторых, наличием абашевского компонента на раннем этапе существования поселения. Это позволяет соотнести начало Мосоловского горизонта с завершающим этапом абашевских древностей. Верхняя граница существования поселения определяется наличием позднесрубных погребений, осуществленных на площади уже заброшенного поселения.
Имеющийся материал позволяет датировать Мосоловский горизонт в пределах третьей четверти II тыс. до н. э. и поместить этот пласт памятников за синташтинским (новоусманским) горизонтом и перед поздневаликовыми памятниками. Выделенный горизонт соответствует развитому этапу срубной культурно-исторической общности алакульской культуры. Findings of the eponymic settlement studied in the forest-steppe Don-river territories (the Voronezh Region) were used for identifying the Mosolovian horizon of relics of the late bronze epoch. A distinct stratigraphic attribution of this site underlies this identification. The lower boundaries of its location are determined first of all by the fact that the settlement of the late bronze epoch is preceded by the settlement of Voronezh AC of the mid bronze epoch and, secondly, by the presence of the Abashev component at the early stage of the settlement existence. This permits correlating the beginning of the Mosolovian horizon with the final stage of Abashev antiquities. The upper boundary of the settlement existence is determined by late Srubian burial grounds made in the territory of the already abandoned settlement.
The findings available permit dating the Mosolovian horizon within the terms of the third quarter of the 2nd millennium B. C. and arranging this layer of relics after the Syntashtininan (Novousmanian) horizon and before late-roller relics. The horizon identified corresponds to the developed stage of the Srubna cultural-historical community of the Alakulian culture.